Sarekat Dagang Islam SDI (1905-1912): Between The Savagery of Vereenigde Oostindische Compagnie (VOC) and The Independence of Indonesia - Muhammad Kaffin Mustakif; Mumung Mulyati (UIN Sunan Gunung Djati Bandung, 2019)
Sarekat Dagang Islam SDI (Islamic Trade Union) was originally an association of native Muslim traders. The organization formed by Haji Samanhudi in Surakarta on October 16, 1905, was initiated with the initial aim of gathering native Muslim traders (especially batik traders) to compete with big Chinese traders. At that time, Chinese merchants were more advanced in business and had higher rights and status than other Indies residents. Policies that were deliberately created by the Dutch East Indies government then led to social change due to the emergence of awareness among the natives. This article discusses how the initial formation of this organization by taking a lengthy historical background; that is, since the entry of the Dutch into the archipelago. This lengthy background was chosen so that the birth of SDI could be understood as the culmination of indigenous disappointment and suffering because of the discriminatory policies of the Dutch colonial government, in addition to other awareness arising from aspects of increasing the level of indigenous education and changing the political atmosphere in the Netherlands. Using a literature survey, this article found that the awareness of native Muslim traders who later gave birth to SDI became the forerunner of the overall indigenous knowledge to obtain independence from the Netherlands. It also led to SDI becoming Sarekat Islam (SI) in 1906 and gaining official recognition from the Dutch government on September 14, 1912. This article captures the historical message that progress of a nation can only occur if the components of the country have a shared awareness to forward through the agreement or national consensus that the formulation is also carried out jointly.